Spirulina and C-phycocyanin mitigate titanium dioxide nanoparticle-induced hematobiochemical and hepatorenal disorders through antioxidative pathway. (October 2022) - Sayed, Amany A.; Soliman, Amel M.; Taha, Mona A.; Sadek, Shimaa A.
Highlights: Post-treatment with spirulina or its active protein, C- phycocyanin, reverse the TiO2 NPs induced- hepatorenal damage. Spirulina and its active protein, C- phycocyanin, exert their hematinic potency as indicated by a marked amelioration in all studied blood indices. The potency of spirulina and C-phycocyanin might be mediated by inhibition of lipid peroxidation and stimulation of the antioxidative defense system. Spirulina is a more effective remedy comparable to its active protein, C-phycocyanin, on attenuation of the hematobiochemical disorders and hepatorenal dysfunction induced by TiO2 NPs exposure. Abstract: The present investigation is designed to evaluate the ameliorative efficacy of spirulina and its active constituent, C-phycocyanin, on hepatorenal injury induced by titanium dioxide nanoparticles (TiO2 NPs). Forty-eight male albino rats were randomly divided into six groups: control group, Spirulina treated group, C-phycocyanin treated group, TiO2 NPs treated group, TiO2 NPs+ Spirulina treated group and TiO2 NPs+ C-phycocyanin treated group. The estimation of hepatic and renal function markers and oxidative status as well as histopathologic alterations in hepatic and renal tissues were analyzed. Spirulina and C- phycocyanin treatments caused significant improvement in all hematological indices such as RBCs, Hb, HCT, and total and differential WBCs relative to the untreated TiO2 NPs group. Also, spirulina and C-phycocyanin treatments significantly alleviated hepatic enzymes and bilirubin concentrations. Oral administration of spirulina and C- phycocyanin decreased total cholesterol and triglycerides content significantly. Both Spirulina and C- phycocyanin attenuated creatinine, urea, and uric acid significantly. Furthermore, the present study revealed that spirulina and C- phycocyanin significantly increased hepatorenal antioxidants content and retard malondialdehyde (MDA) formation. Histopathological examinations displayed that both spirulina and C- phycocyanin treatments repaired mostly the abnormal architecture of hepatic and renal tissues induced by TiO2 NPs. In conclusion, the modulatory role of spirulina and C-phycocyanin may be due to their strong antioxidative effects and other active constituents of spirulina.